Pengembangan Energi Panas Bumi yang Berkelanjutan - Andiesta El Fandari, Arief Daryanto, Gendut Suprayitno (Universitas Muhammadiyah Yogyakarta, 2014)
Electricity consumption in Indonesia increases rapidly in line with population growth. Electricity contribute to promote prosperity and public welfare as well as encouraging increased economic activity. Electricity has played an important role as one of the vital infrastructure that has support of political and economic as a priority. These situations make electricity demand continue to rise. On the other hand, electricity production from fossil fuels have not being able to meet high electricity demand. In accordance with government policies to accelerate infrastructure electricity development without ignoring its sustainability then electricity supply is currently focused on renewable energy development. One of renewable energy is geothermal. As the world’s third largest geothermal electricity producer, it is very unfortunate if that great potential from geothermal development and its utilization still not optimal. This article discusses how the sustainable geothermal energy development in Indonesia. Geothermal energy development as one of the renewable energy becomes very important to be discussed related to fossil fuel reserves are finite, price fluctuations in energy which influenced by world economic and political situation and rising levels of greenhouse gas emission from fuel combustion.